Actor Mapping in Electronic-Based Budgeting Planning in Yogyakarta City (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to analyze the involvement of actors in the implementation of electronic-based budgeting planning (e-planning) which is regulated in several regulations and other policies. As a result of the implementation of e-planning, regional budgeting planning becomes very dynamic from the perspective of actors. This study aims to describe the actors involved in the politics of digitizing electronic-based regional budgeting planning in Yogyakarta City.  The method used is a qualitative approach with data collection techniques through interviews, observations, E-FGD and document data review and analyzed using the Miles and Huberman model. The results of the research found in the form of actors involved in each stage of electronic-based budgeting planning are classified into 3 (three) including executive, legislative and actors outside the government. Executives in the form of the Local Government Budget Team (TAPD) and Regional Apparatus Organizations (OPD). The legislature consists of the institution of the Regional People's Representative Council (DPRD) and personal members of the Council. Meanwhile, actors outside the government are those who have informal power and great influence in society. The interaction of the three is very dynamic and colors the electronic-based budgeting planning according to their respective portions and authorities.